Mobility Programs for the Hospitalized Older Adult: A Scoping Review. (October 2018) - Smart, Denise A.; Dermody, Gordana; Coronado, Melany E.; Wilson, Marian
Objectives: This scoping review (a) describes programs to improve mobility in hospitalized adults and (b) determines the methods used to measure mobility.Method: The Joanna Briggs Institute Methodology for Scoping Reviews was used to conduct this review.Results: Our findings suggest that using a multidisciplinary approach may be the most effective way to promote mobility in hospitalized older adults. Most studies did not articulate how physical activity was measured, indicating that more research is needed.Discussion: The literature shows that implementation of protocols designed to improve the early and regular implementation of physical mobility activities improves the health outcomes of hospitalized older people. Costs associated with healthcare utilization are also reduced, including hospital length of stay. Mobility programs that quantified mobility through validated measurement tools or accelerometers are the most promising as they provide feedback that reinforces progress of the patient and the expected benefits of early mobility.